Iraq Workforce Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
There is a widespread feeling of urgency in Iraq, across the public and private sectors, to improve workforce development (WfD) and the links between education and the work place. However, the country has no clear strategy or plan of action for WfD. The existing WfD structures in Iraq do not have the authority or clear agendas to move forward. In addition, the necessary linkages across technical and vocational education and training (TVET) programs and other types of education or the work place are limited. As a result, Iraq was rated at a Latent stage for all three dimensions on the Systems Approach for Better Education Results (SABER) WfD assessment: Strategic Framework, System Oversight, and Service Delivery.